Drug–Drug Molecular Salt Hydrate of an Anticancer Drug Gefitinib and a Loop Diuretic Drug Furosemide: An Alternative for Multidrug Treatment. Issue 12 (28th September 2015) - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G.
Abstract : A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P ‐1 space group. The CO bond lengths (∼1.26 Å) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong NH···O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of π‐stack dimers. The neighboring dimers are bridged to each other via water molecule through NH···O, CH···O, OH···N, and OH···O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140°C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug–drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4207–4216, 2015